A method of diamorphine (heroin) administration for harm reduction - Oisín N. Kavanagh; Tatiane C. Machado (BMC, 2023)
Abstract As societal attitudes toward narcotics have changed, harm reduction strategies have emerged which make it safer to inject intravenous drugs. Diamorphine (heroin) is commonly sold as its free base-better known as brown-which has extremely poor aqueous solubility. As such, it needs to be chemically modified (cooked) to enable administration. Needle exchange programmes commonly supply citric or ascorbic acids which facilitate intravenous administration by increasing heroin solubility. If heroin users mistakenly add too much acid, the low solution pH can cause damage to their veins and, after repeated injury, could result in the loss of that injection site. Currently, advice cards supplied with these exchange kits suggest that the acid should be measured in pinches, which could result in considerable error. This work employs Henderson-Hasselbalch models to analyse the risk of venous damage by placing solution pH within the context of the buffer capacity of the blood. These models also highlight the significant risk of heroin supersaturation and precipitation within the vein, an event that has the potential to cause further harm to the user. This perspective closes with a modified administration method which could be included as part of a wider harm reduction package.